Parsing financial fragmentation in the euro area: a multi-country DSGE perspective - Matthieu Darracq Pariès; Pascal Jacquinot; Niki Papadopoulou (European Central Bank (ECB), 2016)
The euro area experience during the financial crisis highlighted the importance of financial and sovereign risk factors in macroeconomic propagation, as well as the constraints that bank lending fragmentation would pose for monetary policy conduct in a currency union. We design a 6-region multi-country DSGE model which provides a structural interpretation of the salient features of these developments. The model spans the relevant "financial wedges" at play during the crisis, together with its cross-country heterogeneity within the euro area, focusing on Ger- many, France, Italy, Spain, and rest-of-euro area. We construct three stylised macro-financial scenarios as a synopsis of the euro area financial crisis and argue that the adverse interactions between sovereign, banking and corporate risk, can account to a large extent for the financial repression and poor economic performance observed in some parts of the euro area.
Keywords: E4; E5; F4; 330; bank lending rates; banking; cross-country spillovers; DSGE models; financial regulation